Answer:
Step-by-step explanation:
lets replace x with 3
f(3)= -2(3)^3+3(3+2)=-2*27+15=-54+15=-39
Answer:
2
Step-by-step explanation:
Answer:
→ The table is:
→ x → -1 → 0 → 1
→ y → -3 → 0 → 3
The graph of the line is figure d
Step-by-step explanation:
∵ y = 3x
∵ x = -1, 0, 1
→ Substitute the values of x in the equation to find the values of y
∴ y = 3(-1) = -3
∴ y = 3(0) = 0
∴ y = 3(1) = 3
→ The table is:
→ x → -1 → 0 → 1
→ y → -3 → 0 → 3
∵ The form of the linear equation is y = m x + b, where
∵ y = 3x
→ Compare the equation with the form
∴ m = 3
∴ b = 0
→ That means the slope is positive, then the direction of the line must
be from left tp right and passes through the origin
∴ The graph of the line is figure d
Answer:
- C. The surface area of the pyramid is multiplied by 100
Step-by-step explanation:
The area is the function of the two dimensions.
If each dimension has changed by 10 times, the the area will change by:
Correct choice is C